2015
DOI: 10.1016/j.dnarep.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Role of mismatch repair proteins in the processing of cisplatin interstrand cross-links

Abstract: Mismatch repair (MMR) deficiency gives rise to cisplatin resistance and can lead to poor prognosis in cancers. Various models have been proposed to explain this low level of resistance caused due to loss of MMR proteins. We have shown that MMR proteins are required to maintain cisplatin interstrand cross-links (ICLs) on the DNA leading to increased cellular sensitivity. In our previous studies, we have shown that BER processing of the cisplatin ICLs is mutagenic. Polymerase β (Polβ) can generate mismatches whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 39 publications
2
58
1
Order By: Relevance
“…Emerging data indicate that RPRD1B plays an important role in several DNA repair mechanisms, including double-strand breaks (DSB) repair through the association with core non-homologous end joining (NHEJ) proteins (45) and mismatch repair (46). Defects in RPRD1B expression or knockdown cause a deficiency in DNA repair mechanisms known to be critical in resolving cisplatin-induced lesions (47). Consistent with our data indicating low levels of RPRD1B being associated with CisIPN, knockdown of this gene in a breast cancer cell line, MDA-123 results in increased sensitivity to cisplatin (45).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data indicate that RPRD1B plays an important role in several DNA repair mechanisms, including double-strand breaks (DSB) repair through the association with core non-homologous end joining (NHEJ) proteins (45) and mismatch repair (46). Defects in RPRD1B expression or knockdown cause a deficiency in DNA repair mechanisms known to be critical in resolving cisplatin-induced lesions (47). Consistent with our data indicating low levels of RPRD1B being associated with CisIPN, knockdown of this gene in a breast cancer cell line, MDA-123 results in increased sensitivity to cisplatin (45).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fact that cell viability was similar for GM04312 and A2780 cells following cisplatin treatment suggests that other repair pathways (different from NER) could be contributing to the cisplatininduced DNA damage response, at least at low doses. 10,22 Despite similarities in cell viability with the GM04312 cells, the sensitivity of the A2780 cells to cisplatin cannot be linked to a deficiency of DNA repair. However, it might be related to their higher Pt influx, as described, 27,37,42,43 even for other platinum chemicals, 44 which could be related to high levels of the copper transport protein CTR1, 23 although recently the influence of this type of protein was considered controversial.…”
Section: Discussionmentioning
confidence: 99%
“…34 However, detection of DNA strand breaks after cisplatin treatment is not a straightforward result; some authors reported them in different cells and organisms, 20,26 and others reported their absence. 20,51,52 Although some authors have used the Comet assay to detect and quantitate cisplatin-induced DNA adducts, 15,22,51 we have used it to study which DNA adduct levels would induce detectable genomic instability. Our results show that cisplatin induced DNA strand breaks only in GM04312 cells at AT-1 time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that Polβ misincorporates dATP at ~1.6 fold higher frequency as compared to the correct nucleotide base dCTP opposite guanine near the ICL site [5]. The generation of these mismatches leads to increased recruitment of MMR proteins and a subsequent role of MMR in blocking productive cisplatin specific ICL repair [12, 20]. The binding of BER and MMR proteins results in a futile cycle at the ICLs by blocking the productive ICL DNA repair pathways, resulting in the persistence of DNA ICLs which give rise to enhanced cisplatin cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%